Employment Nondiscrimination Acts and Corporate Innovation - Gao, Huasheng (2017)
We show that U.S. state-level employment nondiscrimination acts (ENDAs)—laws that prohibit discrimination based on sexual orientation and gender identity—spur innovation. We find a significant increase in patents and patent citations for firms headquartered in states that have passed ENDAs relative to firms headquartered in states that have not. This result is more pronounced for firms that previously have not implemented pro-gay nondiscrimination policies, for firms in states with a large homosexual population, and for firms in human capital-intensive industries. Lastly, we provide evidence suggesting that ENDAs affect innovation by matching employees, who are generally more creative than anti-gay employees, with innovative firms.